Exploiting the dividend month premium: evidence from Germany - Kreidl, Felix; Scholz, Hendrik (Journal of Asset Management, 2021)
Dividend payments are firm events on a recurring and predictable basis. High returns in the period between announcement-date and ex-dividend date are the main driver for the so-called dividend month premium, which are positive abnormal returns in months in which corporations are predicted to issue dividend payments. In our empirical analysis of the German stock market, we find a robust dividend month premium, which is particularly high for stocks with positive dividend surprise. Knowing the dates of dividend announcements and payments enable portfolio managers to exploit the dividend month premium. Also taking into account tracking error and transaction costs, we show that simple portfolio-enhancing strategies lead to highly significant abnormal returns.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Cumulative abnormal returns; Dividend month premium; Dividend surprise; Dividends; Exploitation; Outperformance; Portfolio management